StopBlues: a French e-health device to prevent suicide in the general population. (13th November 2019) - Le Jeannic, A; Gandré, C; Vinet, M A; Turmaine, K; Roelandt, J L; Giraudeau, B; Alberti, C; Chevreul, K
Abstract: Background: France is one of the Western European countries most affected by suicide, an epidemiological burden and high societal cost of several million euros/year. Several European projects have either implemented web-based interventions for care of mental disorders or recommended online actions which have demonstrated their effectiveness for suicide prevention. The objective of the project was the construction of an application and website to prevent suicide in the general population, with its promotion being supported at the local authority level. Methods: The detailed content of the devices and promotional tools available to local authorities was determined through literature reviews and expert groups (psychiatrists, local authorities' workers and potential users). Results: An application and website were constructed with two parts: a public interface with videos (psychological suffering, coping strategies and help available), an emergency button, a map with local resources and contact information (psychiatrists, psychologists, associations...), tips and videos to overcome a period of psychological suffering; and a private interface requiring registration giving access to self-assessment questionnaires and a safety plan to fill in case of crisis. 40 local authorities are involved in StopBlues promotion, with a referent each, responsible of contact with our team, and local organization of promotion. Conclusions: Since 04-2018, StopBlues is available at www.stopblues.fr and can be downloaded on iOs and Android. Its promotion is part of a cluster randomized trial with 3 arms: a control group with no promotion, a group with promotion by local authorities, and a group with promotion by local authorities and general practitioner's waiting room. As promotion could have different intensities depending on budgets and referent's involvement, we decided to extend it for another year, with local authorities of group control receiving additional financial and organizational support. Key messages: As the first e-health program for suicide primary prevention in the French general population, StopBlues' main goal is to help people find solutions that suit them and direct them to the right help. Local authorities are a key level to promote primary health prevention programs.